ChemInform Abstract: Depsidone and Diaryl Ether Derivatives from the Fungus Corynespora cassiicola, an Endophyte of Gongronema latifolium. Issue 46 (24th October 2013) - Okoye, Festus Basden C.; Lu, Su; Nworu, Chukwuemeka S.; Esimone, Charles O.; Proksch, Peter; Chadli, Ahmed; Debbab, Abdessamad
Abstract isolation and structure elucidation of corynesidone D (I), corynether B (II) and corynether lactone A (III)